Idiopathic Extensive Abdominal Aortic Thrombosis with Extension to the Celiac Trunk and Mesenteric Arteries in a Previously Healthy Female - Naima Mustafa Abdi; Mohamad Shieb; Masoud Shafiei (Dubai Medical Journal)
Idiopathic arterial thrombosis is frequently encountered in clinical practice after all investigations and imaging have been exhausted and yet no underlying etiology could be found. This article discusses the case of a 32-year-old healthy female who presented with symptoms of acute-onset abdominal pain and vomiting, which, after conducting an extensive series of investigations, were attributed to an extensive abdominal aortic thrombosis of unknown etiology. Prompt diagnosis of acute aortic thrombosis is of high importance due to the unpreferable prognosis in case of delay in treatment. Despite the high mortality and morbidity rates associated with this condition, better clinical outcome correlates with earlier identification and management. This mandates having individualized treatment for each patient depending on the presentation, age, etiology of the thrombosis, and patient’s comorbidities.